2016
DOI: 10.1007/s00128-016-1921-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Soil Amendments on Mixed Heavy Metals Contamination in Vetiver Grass

Abstract: Three different types of low cost soil amendments, namely, EDTA, elemental S and N-fertilizer, were investigated with Vetiver grass, Vetiveria zizanioides (Linn.) Nash growing under highly mixed Cd-Pb contamination conditions. A significant increase (p < 0.05) in Cd and Pb accumulation were recorded in the shoots of all EDTA and N-fertilizer assisted treatments. The accumulation of Cd in 25 mmol EDTA/kg soil and 300 mmol N/kg soil showed relatively higher translocation factor (1.72 and 2.15) and percentage met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
6
2
Order By: Relevance
“…37,38 Among the different plants, Vetiver (13.55%-32.52% of Cd and 34.51%-45.05% of Pb) recorded remarkably higher percentages for both Cd and Pb metal efficacy than both Mucuna (15.52%-25.44% of Cd and 22.83%-35.41% of Pb) and Acacia (13.10%-20.61% of Cd and 15.63%-29.59% of Pb), respectively. The positive characteristics of Vetiver with fast growth, good tolerance, and its ability to withstand high concentration levels of soil-leachate conditions were similarly reported in previous works 30,31,39,40 and Vetiver remained to be the most promising species compared with the other tropical plants studied for the use in soil-leachate phytoremediation.…”
Section: Resultssupporting
confidence: 81%
“…37,38 Among the different plants, Vetiver (13.55%-32.52% of Cd and 34.51%-45.05% of Pb) recorded remarkably higher percentages for both Cd and Pb metal efficacy than both Mucuna (15.52%-25.44% of Cd and 22.83%-35.41% of Pb) and Acacia (13.10%-20.61% of Cd and 15.63%-29.59% of Pb), respectively. The positive characteristics of Vetiver with fast growth, good tolerance, and its ability to withstand high concentration levels of soil-leachate conditions were similarly reported in previous works 30,31,39,40 and Vetiver remained to be the most promising species compared with the other tropical plants studied for the use in soil-leachate phytoremediation.…”
Section: Resultssupporting
confidence: 81%
“…In contrast, Lai and Chen (2004) found no significant influence with the application of EDTA at 5 and 10 mmol/kg soil for both Zn and Pb accumulations in Vetiver grass. However, the application of 5 and 25 mmol/kg of EDTA by Chen et al (2004c) and Ng et al (2016) recorded reasonably higher concentrations of Pb and Cd in Vetiver grass, respectively. Moreover, the findings of this study also showed that soil pH became more acidic in all the single and mixed heavy metal treatments when EDTA was added as compared to the control.…”
Section: Discussionmentioning
confidence: 87%
“…In terms of soil amendment, although the possible outcomes for heavy metal phytoaccumulation may increase with EDTA, a standard composition of 10 mmol EDTA/kg was selected in this study based on the research findings obtained in Grčman et al (2001) and Ng et al (2016). The artificially spiked soil was then repeatedly stirred and incubated for a fortnight to achieve the homogeneity of the desired single and mixed heavy metal soils are obtained.…”
Section: Soil Management and Sampling Preparationmentioning
confidence: 99%
See 2 more Smart Citations